2019
DOI: 10.1002/cplu.201800636
|View full text |Cite
|
Sign up to set email alerts
|

The Counterion Effect of Imidazolium‐Type Poly(ionic liquid) Brushes on Carbon Dioxide Adsorption

Abstract: Imidazolium‐based poly(ionic liquid) brushes were attached to spherical silica nanoparticles bearing various functionalities by using a surface‐initiated atom transfer radical polymerization (“grafting from” technique). A temperature‐programmed desorption process was applied to evaluate and analyze the carbon dioxide adsorption performance of the synthesized polymer brushes. The confined structure of the surface‐attached polymer chains facilitates gas transport and adsorption, leading to an enhanced adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The CO 2 adsorption behavior was performed on a TPD apparatus TP-5080 (Tianjin Xianquan, China) using helium as carrier gas. The typical procedure includes pre-adsorption of CO 2 at desired temperature under CO 2 partial pressure of 0.2 bar, followed by temperature-dependent desorption and finally complete desorption of the adsorbed CO 2 molecules at 200 • C. The detailed procedure was described elsewhere [43]. The adsorbed amount of CO 2 was calculated from the detected TPD signals of thermal conductivity detector using the software from the supplier.…”
Section: Co 2 Adsorptionmentioning
confidence: 99%
“…The CO 2 adsorption behavior was performed on a TPD apparatus TP-5080 (Tianjin Xianquan, China) using helium as carrier gas. The typical procedure includes pre-adsorption of CO 2 at desired temperature under CO 2 partial pressure of 0.2 bar, followed by temperature-dependent desorption and finally complete desorption of the adsorbed CO 2 molecules at 200 • C. The detailed procedure was described elsewhere [43]. The adsorbed amount of CO 2 was calculated from the detected TPD signals of thermal conductivity detector using the software from the supplier.…”
Section: Co 2 Adsorptionmentioning
confidence: 99%
“…Over the past 10 years, various sorbents derived from both linear [ 4 , 17 , 18 , 19 ] and cross-linked [ 20 , 21 , 22 ] PILs have been investigated (see the examples in Scheme 1 and in Table 2). To enhance PILs’ CO 2 sorption capacity, a number of approaches have been applied, such as PILs’ immobilization on carbon fibers [ 23 , 24 ], grafting of PILs on silica nanoparticles [ 25 , 26 , 27 ], incorporation of PILs into a metal–organic framework (MOF) [ 28 , 29 , 30 , 31 ] or preparation of ordered porous PIL-based crystallines [ 32 ]. It was found that the CO 2 adsorption behavior of PILs is dependent on many factors, such as their chemical composition (nature of the cation and anion, type of the polymer backbone), molar mass and pore structure (surface area, pore size, atomic packing, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the counter anion has a pronounced effect on the CO 2 sorption of PILs as well. This was widely studied using such anions as R 1 COO (R 1 =CF 3 , C 3 F 7 , CH 3 ), R 2 SO 3 (R 2 =CF 3 , CH 3, C 6 H 4 -), (CF 3 SO 2 ) 2 N, BF 4 , PF 6 , NO 3 , N(CN) 2 , B(CN) 4 , FeCl 3 Br, ZnCl 2 Br, CuCl 2 Br [ 14 , 15 , 16 , 18 , 19 , 27 , 35 , 36 ]. Among this vast variety of anions, the best CO 2 uptake was demonstrated by CH 3 COO, B(CN) 4 , BF 4 and PF 6 containing PILs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, solid sorbents attracted research attention due to their safety, good cyclability, high selectivity, and convenience for transport and storage [9,10]. As an example, amine-functionalized porous materials were realized as efficient solid sorbents for carbon dioxide adsorption [11,12,13,14,15,16,17,18,19,20,21]. Particularly, metal–organic framework (MOF)-based functional materials exhibited great adsorption capability for carbon dioxide due to their large surface area (even above 2000 m 2 ·g −1 ), the similar pore size to the dynamic diameter of carbon dioxide molecules, and the interaction between carbon dioxide molecules and the imidazolium moieties on MOF-based compounds [22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%